Type I caramel products of fructose with water and their bioactivities - LI, Tian-Xiao; HUANG, Jia-Le; WU, Lei; JI, Ling-Bo; SHENTU, Hong-Qian; HE, Bao-Jiang; JIANG, Zhong-Rong (Food Science and Technology, 2023)
To investigate the fructose-water caramel reactions, the type I fructose caramel products (FCPs) were prepared and collected at different reaction stages. The reaction rate, caramel flavor compounds, UV absorptions, antioxidant, and antibacterial activities were determined. The results showed that the reaction rate was increased quickly to 90.1% at the end of middle stage. The exponentially growth of UV305nm suggested the caramel pigments and flavor compounds were rapidly formed along with the reaction. The FCP obtained at arriving of 180 °C possessed the highest contents of total flavor compounds and 5-hydroxymethylfurfural, and the fructose caramel reaction was fast than those of glucose. Total eight characteristic caramel flavor compounds were revealed from FCPs and their formation pathway were also speculated. An optimized condition was suggested at arriving of 180 °C and the FCP under this condition also exhibited potent antioxidant and antibacterial activities. All these results suggested that such kind of type I fructose caramel products could be used as food additive in food industry for the further development.